Undergraduate Students Citation Writing Difficulties - Suntoro Suntoro; Ida Zulaeha; Hari Bakti Mardikantoro; Tommi Yuniawan (Universitas Negeri Semarang, 2023)
Writing citations is one of the skills that must be developed by students to be able to do research well. The fact is that there are still many students who need help writing citations. This study aims to identify students' difficulties in writing citations. The research method used was a mixed method with data collection instruments in the form of questionnaires distributed to 68 respondents and 10 student research proposal documentation. Data analysis was carried out by analyzing quantitative data first by making a description of the level of difficulty and type of difficulty in writing citations in the form of a percentage with the help of SPSS and then elaborating using qualitative data to draw conclusions then. The results of the research show that: (1) students think that writing citations is a problematic competency; (2) the percentage of student difficulties in writing citations from the largest to the smallest includes: (a) identification and evaluation of credible and non-credible references of 26.4%, (b) determining and finding relevant reference sources of 21.7%, (c) technical writing of citations by 20.8%, (d) synthesis and analysis of citations by 13.2%, (e) determining the attitude or position of the author of several citations made by 12.3%, and (f) paraphrasing citation of 5.7%. The root of the problem in citation writing is the need for students to determine and find relevant and credible reference sources, which results in difficulties in analyzing, synthesizing, and determining attitudes. While technical difficulties related to writing are more caused by writing citations manually without using reference manager software, difficulty understanding foreign languages, and many citations that need to be reported or accompanied by sources.